Observational methodology in sport sciences - M. Teresa Anguera; Antonio Hernández Mendo (Federación Extremeña de Balonmano; University of Extremadura, 2013)
This paper reviews the conceptual framework, the key literature and the methods (observation tools, such as category systems and field formats, and coding software, etc.) that should be followed when conducting research from the perspective of observational methodology. The observational designs used by the authors' research group over the last twenty years are discussed, and the procedures for analysing data and assessing their quality are described. Mention is also made of the latest methodological trends in this field, such as the use of mixed methods.